O texto autobiográfico em sala de aula do Ensino Fundamental - Rocha, Flávia Cavalcante (2018)
With this work, we aim to contribute to the teaching and learning of writing through the production of autobiographical texts by students of the 9th grade of Middle School of a public school in Fortaleza-CE. We conceived a didactic sequence, based on the proposal of Dolz, Noverraz and Schneuwly (2004), as a methodological resource to verify students' performance in written texts as well as to prove the efficiency of such procedure as a teaching proposal. Thus, in order to develop students' competence in the production of texts, especially the written ones, we also follow the guidelines of the National Curriculum Parameters of the Portuguese Language, and more recently the National Curricular Common Base, which guide the work with textual genres in the classroom and certify that it is necessary to contemplate the diversity of texts and genres, not only because of their social relevance, but also because texts belonging to different genres are organized in different ways. We present, then, activities directed to the work with the autobiography genre in the classroom. From this perspective, we work on writing production, intending to value the students' identity and emphasize their importance as participatory and critical individuals in the society where they live. In summary, this work proposes to invest in the improvement of reading and writing practices and can be constituted as a pedagogical initiative of application of the Ideological Model of Literacy advocated by Street (2014).